2022
DOI: 10.1080/16549716.2022.2122304
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of community health participatory research projects in Ghana

Abstract: Background Community health participation is an essential tool in health research and management where community members, researchers and other relevant stakeholders contribute to the decision-making processes. Though community participation processes can be complex and challenging, evidence from previous studies have reported significant value of engaging with community in community health projects. Objective To identify the nature and extent of community involvement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Second, it is necessary to continue our efforts to go further in involving local communities in health interventions to ultimately improve health outcomes ( 34 ). In particular, for the epidemiological studies needed to establish appropriate and evaluable health studies and interventions, we need to improve the level of community participation and progress toward interactive participation ( 33 ). This requires the promotion of intercultural dialog between Western and Traditional communities, through study co-design and evaluation and the establishment of a sustainable climate of trust and partnership ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is necessary to continue our efforts to go further in involving local communities in health interventions to ultimately improve health outcomes ( 34 ). In particular, for the epidemiological studies needed to establish appropriate and evaluable health studies and interventions, we need to improve the level of community participation and progress toward interactive participation ( 33 ). This requires the promotion of intercultural dialog between Western and Traditional communities, through study co-design and evaluation and the establishment of a sustainable climate of trust and partnership ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in such a situation, if they accept the lifestyle and rules of local healthcare providers, international healthcare volunteers may feel that it can be easier to adapt to the local situation. Previous studies showed that international healthcare volunteers first need to understand and accept local culture to play health-related roles [ 27 ]. Thus, accepting local cultural norms is essential to continuing outreach programs in low-income countries [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Research Buddy program reflected upon in this piece took the approach of broadening the perspective of the research team by including the voice a patient with lived experience of a health condition [ 43 ]. This is distinct from an approach which would seek to achieve representativeness from one patient partner on behalf of all patients with a shared lived experience, which would be unrealistic [ 31 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Early involvement has been demonstrated or recommended numerous times in a diverse range of contexts and for different levels of involvement [ 5 , 7 , 15 , 28 , 35 , 43 , 75 ].…”
Section: Methodsmentioning
confidence: 99%